The Effects of Hyperbaric Oxygen Therapy on Pelvic Radiation Induced Gastrointestinal Complications (Rectal Bleeding, Diarrhea, and Pain): A Meta-Analysis - Yuan, Jun-hua; Song, Li-min; Liu, Yuan; Li, Man-wen; Lin, Qian; Wang, Rui; Zhang, Cai-shun; Dong, Jing (Frontiers in Oncology, 2020)
Background: Radiotherapy is a routine treatment for pelvic cancer patients. While it had been proven effective, gastrointestinal side effects remain a concern, impairing the quality of life. A few studies focused on the effects of hyperbaric oxygen (HBO) treatment to alleviate radiation-induced gastrointestinal complications. This meta-analysis aimed to critically review and summarize existing literature, assessing the effectiveness of HBO therapy for the treatment of radiation-induced gastrointestinal side effects. Methods: Medical literature search was performed with PubMed, Cochrane Library, and EMBASE up to March 14, 2019. Literatures about HBO treatment upon patients undergoing pelvic cancer (endometrial, cervix, rectum, or prostate cancers) radiotherapy were collected, and the effects of HBO treatment on radiotherapy-induced gastrointestinal complications were evaluated. A random-effects model was used to calculate the pooled effect size. Subgroup analyses were performed to search for sources of heterogeneity. Publication bias was detected with Funnel plots and Egger's test. Results: Three different radiotherapy-related gastrointestinal complications, including rectal bleeding, diarrhea, and pain, were analyzed after screening. It was revealed that the improvement rates were considerable in rectal bleeding (0.81, 95% CI: 0.74–0.89) and diarrhea (0.75, 95% CI: 0.61–0.90) and slightly in pain (0.58, 95% CI: 0.38–0.79). Subgroup analysis revealed factors that significantly influenced the heterogeneity of rectal bleeding, diarrhea, and pain (evaluation criteria, follow-up time, and scoring system, respectively). No significant publication bias was detected. Conclusion: HBO treatment might have the potential to alleviate radiotherapy-related gastrointestinal complications, including rectal bleeding, diarrhea, and pain, but more data are needed for further conclusions. Other symptoms were not further analyzed, as the number of studies was insufficient. More large-scale and prospective studies are needed for better evaluation of HBO's therapeutic values.